Population-Level Incidence and Use-Related Factors of Comfort and Orthopedic Accessories Among Older Vehicle Occupants in NSW, Australia. (October 2021) - Sran, Raman; Keay, Lisa; Coxon, Kristy; McAuley, James; Whyte, Tom; Brown, Julie
The proportion of people aged 65 years and older regularly traveling in motor vehicles continues to grow worldwide. In a previous convenience sample, we observed many older people using comfort accessories when traveling in vehicles, and these may contribute to the known increased risk of injury in crashes among older people. In this study, we aimed to estimate population-level use of these devices and examine associations between demographic, health, and travel behavior factors and their use. The point estimate of self-reported use of comfort accessories was 25.7% (95% confidence interval [CI] = [19.6%, 31.9%]). Cushions on the vehicle seat were the most common type used (14.3%, 95% CI = [9.7%, 19.0%]), and increasing age, female gender, and frequent vehicle travel were significantly associated with their use. Less frequently used were seat belt padding (10.5%, 95% CI = [6.3%, 14.6%]) and back/neck supports (6.5%, 95% CI = [2.7%, 10.2%]). Back/neck and multiple area pain were significantly associated with the use of the latter.